Enhancing the Nutritional Quality of Low-Grade Poultry Feed Ingredients Through Fermentation: A Review - Jim Kioko Katu; Tamás Tóth; László Varga (Agriculture)
Feed accounts for up to 80% of poultry production costs, with high-quality grains such as soybean meal and corn traditionally serving as primary ingredients. However, increasing costs and competition for these grains have driven interest in low-grade and unconventional feed ingredients, including by-products like rapeseed meal and cottonseed meal. These alternatives are often constrained by high fiber content, anti-nutritional factors, and reduced nutrient bioavailability. Fermentation has emerged as a promising strategy to address these limitations, enhancing digestibility, palatability, and antioxidant properties while degrading harmful compounds such as tannins, trypsin inhibitors, and free gossypol. Solid- and liquid-state fermentation techniques utilize microbial inoculants, including lactobacilli and Bacillus species, to enzymatically break down complex macromolecules, thereby releasing essential nutrients. When combined with pretreatments like enzymatic hydrolysis, fermentation significantly improves the nutritional quality of feed ingredients while reducing costs without compromising poultry health or performance. This review examines the mechanisms, benefits, and challenges of fermentation techniques in poultry feed production, underscoring the importance of further research to optimize fermentation parameters, identify novel microbial strains, and ensure scalability and safety in industrial applications.